Food subsidies: Consumer welfare and producer incentives - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1988)
Policies to strengthen incentives to expand food production through higher food prices are likely to result in short-run reductions in real incomes of food consumers. Since a large share of the income of the poor is generally spent on food, higher food prices may cause severe hardships to those who do not derive their incomes from food production either directly as producers or farm workers or indirectly as providers of inputs and consumption goods to farmers. But not only the poor will be adversely affected. Food expenditures of the better-off consumers also will rise as food prices increase. Although the poor will have a larger loss relative to current incomes, their absolute loss will be smaller.